The impact of environmental information disclosure on enterprises’ green preference of outbound investment: Evidence from China - Cheng Peng; Cheng Peng; Wenting Fu; Wenting Fu; Hui Jiang; Yu Zou (Frontiers in Psychology, 2022)
China is accelerating green and low-carbon transformation and promoting high-quality economic development. To effectively contribute to the improvement of global environmental quality and enhance enterprises’ awareness of environmental responsibility in the process of outbound investment, China strongly advocates that enterprises should comply with the environmental protection laws and regulations of host countries and try to strengthen local environmental protection as investing abroad. However, inadequate attention has been paid to the factors influencing green preferences in corporate outbound investment. Therefore, using a sample of Chinese A-share listed companies from 2008 to 2019, this paper aims to empirically analyze whether the quality of environmental information disclosure (QEID) affects enterprises’ green preference of outbound investment (OIGP), and the influence mechanism of QEID on the enterprises’ OIGP by analyzing the mediating effects of green technology innovation and media attention. It is found that QEID significantly promotes corporate OIGP. In terms of influence mechanism, QEID promotes firms’ OIGP by restraining media attention, while the mediating role of green technology innovation in the effect of QEID on firms’ OIGP is manifested as the masking effect. In addition, it is found that these influence mechanisms are different among enterprises with different property rights and different life cycle stages.